Qualitative communication research methods - Lindlof, Thomas R.; Taylor, Bryan C. (SAGE Publications, Inc., 2019)
Qualitative Communication Research Methods, Fourth Edition introduces readers to qualitative research in speech and mass communication, providing numerous examples of work in the field to illustrate how studies are designed, carried out, written, evaluated, and related to theory.